Positive association of female overactive bladder symptoms and estrogen deprivation: A nationwide population-based cohort study in Taiwan. Issue 28 (July 2016) - Cheng, Chen-Li; Li, Jian-Ri; Lin, Ching-Heng; de Groat, William C.
Abstract: Objective: Estrogen is considered to be a unique hormone in females that has an impact on voiding function. Animal models and clinical epidemiologic studies showed high correlation between estrogen deficiency and female overactive bladder (OAB) symptoms. We designed a population-based cohort study from a national health database to assess the association of estrogen deprivation therapy and female OAB. Materials and methods: This study examined the records of 16, 128 patients ranging in age from 18 to 40 that were included in the Taiwan National Health Insurance Research Database (NHIRD) in the years between 2001 and 2010. Of these, 1008 had breast cancer with hormone therapy only and the other 15, 120 controls did not have breast cancer or hormone therapy. All patients with neurologic diseases and those with pre-existing OAB identified by information in the NHIRD database were excluded. OAB was defined by medications prescribed for at least 1 month. Risk of new onset OAB in the breast cancer and nonbreast cancer groups was estimated. Fourteen patients (1.4%) experienced OAB in the breast cancer group. Overall, breast cancer with estrogen deprivation therapy increased the risk of OAB by 14.37-fold (adjusted hazard ratio, 95% confidence interval 7.06–29.27). Subgroup analysis showed that in the older age breast cancer group (36–40), a lower Charlson comorbidity index (CCI) score and antidepressant medication use for at least 30 days had an impact on the increase of OAB risk. After adjustment of variables, the higher CCI and the use of antipsychotic drugs increased risk of OAB 3.45-fold and 7.45-fold, respectively. The Kaplan–Meier analysis of OAB-free survival in the breast cancer group showed a significant time-dependent increase in incidence of OAB. Conclusion: Estrogen deprivation in young patients with breast cancer increased the risk of OAB. The OAB development rate was steady and fast in the beginning 3 years after estrogen deprivation. This result indicates a role of estrogen in the modulation of female voiding function.